Strengthening the Profile of Pancasila Students with Global Diversity at Learning Studio Sentul Malaysia - Ambiro Puji Asmaroini; Sulton Sulton; Dian Kristiana; Shohenuddin Shohenuddin; Benjamin Laurentino Vaz (STAI Hubbulwathan Duri, 2024)
Sentul Learning Studio is a form of tutoring for undocumented migrant children to obtain an education. The ethnic and linguistic diversity enhances the profile of Pancasila students with global diversity, as teachers incorporate this into their teaching. This research aims to understand how teachers contribute to strengthening the Pancasila Global Diversity student profile in Malaysian learning centers. The study utilizes a qualitative research method. Research findings show that raising the profile of Pancasila students with global diversity involves understanding and valuing various cultures, engaging in intercultural communication during interactions, and reflecting on and taking responsibility for diverse experiences. Conclusion This research explores the implementation of the Merdeka Curriculum, which allows Pancasila education teachers at the Sentul Malaysia learning center to design student-tailored learning experiences. The center originally had 7 students, increasing to 13, 24, 37, and now 41 students, with 6 students currently inactive. The curriculum emphasizes global diversity competencies. Teachers integrate Indonesia's cultural heritage through activities such as traditional dances and games, including the Jathilan dance and the Ampar-Ampar Pisang folk song. Two students are fluent in Javanese and Indonesian. Activities such as celebrating Mother's Day and making crafts from recycled materials foster curiosity about Indonesian culture. Gymnastics and games with Indonesian roots such as Senam 123, Gemo Famire, and penguin gymnastics are also included. Learning the Jathilan dance, jumping rope, and making soybean tempeh exposes students to authentic Indonesian culture, fostering acceptance, appreciation, and a desire to learn.